How does company misconduct affect company survival risk?-evidence from China. - Ling Lu (PLoS ONE)
Based on the data of China's listed companies from 2000 to 2022, this study investigates how company misconduct affect company survival risk through survival analysis. The research results show that company misconduct significantly increases company survival risk. After considering endogeneity issues and conducting robustness tests, this conclusion still holds. Mechanism analysis reveals that company misconduct significantly increases enterprise survival risk by reducing investor confidence and increasing corporate financing constraints. Further analysis considering company and regional heterogeneity, which shows that non-state-owned, small-scale, low equity concentration, and eastern region company face more severe survival risk after misconduct. The findings extend the research on the influencing factor of company survival, and provide new empirical evidence for revealing how corporate misconduct affect company survival risk.